Short stature among girl child: a psychological burden or a social stigma-a review - Sharma, Karishma; Singh, Brijendra; Naithani, Manisha; Chandra, Rishita; Verma, Prashant K. (International Journal Of Community Medicine And Public Health, 2021)
Short stature (SS) is defined as “height below the third percentile or less than two standard deviations below the median height for that age and sex according to the population standard”. Short stature is not itself a pathology or disease but sometimes may be present as a manifestation of some underlying pathological condition. This condition is seen to impact adversely on the psychological wellbeing of the affected individuals and gives rise to the social stigma which further worsens the quality of life of short-statured persons. Hence, there is a need to acknowledge and break this stigma thereby improving the psychological wellbeing of the short-statured population.